Perbandingan Penggunaan Tes Objektif dan Tes Subjektif terhadap Hasil Belajar - Magdalena, Ina; Aqmarani, Andini; Nurhalisa, Nurhalisa; Syahra, Nazwakhairy Putri (Lembaga Yasin AlSys, 2023)
Assessment tries to determine whether or not educational goals are achieved, so that assessment plays a very important role in the world of education. Each subject emphasizes continuous assessment related to holistic goals and outcomes. This study aims to determine the results of the process of compairing learning outcomes using objective tests and those using subjective tests, because the use of tests greatly influences student learing outcomes and how efficiently the test results are used against students’ abilities in mastering the material. From teaching materials. The method used is library research. A number of references are based on assessments of cognitive learning outcomes from books, journals, and related government regulatory documents. The results of the study show that based on several references to journals and books that the author has collected from various sources, it can be concludes that objective tests and subjective tests have the same use if they are correct ini selectibg questions. Because there are students who do not concentrate in the daily learning process, so that in objective tests student can choose answers with conjecture guessing techniques. While this subjective test can train students’ mindsets, can develop their knowledge, can train children to arrage words into appropriate senteces and can help children to improve the assessment of learning outcomes